Agricultural extension: is it still relevant? - Zahara Tussoleha Rony; D. Yadi Heryadi (Faculty of Communications Science, Dr. Soetomo University, 2024)
Abstract The rapid development of Artificial Intelligence (AI) and automation systems in the digital world challenges agricultural extension. This study investigates the contemporary significance of diverse and productive agriculture, specifically focusing on agricultural extension. This study investigates the implementation of agricultural extension services in Indonesia's automation, digital, and adapting environments through a comprehensive review of existing literature. Studies have indicated that agricultural extension plays a crucial role in mitigating climate change. This study assesses the effectiveness of agricultural extension services in different environments in Indonesia through qualitative research methods. Information was gathered by conducting interviews, surveys, and field observations. The results demonstrate the indispensability of agricultural extension in all types of environments, particularly in addressing climate change. It has been ascertained that each environment necessitates distinct educational approaches. Digital environments prioritise acquiring technical knowledge, automation environments necessitate education in sustainable agricultural practices, and adapting environments prioritise integrating field experience and local knowledge. This study provides an extensive review of the functions of agricultural extension. It demonstrates that agricultural extension can combat climate change. Furthermore, it underscores the importance of employing educational methods and approaches tailored to the specific environment, as this will influence the development of agricultural extension education.